Komparasi Atraksi Wisata 3 Pilar Ikon Wisata Kota Surabaya - Abdullah Alba Saiba; Fabian Nugroho; Achmad Syahfrizal; Mohammad Insan Romadhan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The number of tourist visits to Surabaya City continues to increase every year, demanding the development of tourist attractions that can strengthen the city's appeal as a leading tourist destination in East Java. This study aims to compare three iconic pillars of Surabaya's tourism: Jl. Tunjungan as an urban heritage icon, Gunung Sari Mangrove Forest as a natural attraction, and Taman Cahaya as an educational and recreational green space. The results of this research can serve as a reference for developing destination attractions and facilities, as well as forming the basis for promotional strategies to enhance visitor numbers, length of stay, and expenditure. Data were analyzed using a quantitative descriptive approach and multiple linear regression. The analysis reveals that both tourist attractions and tourist motivations significantly influence visitation decisions, both simultaneously and partially. Among the three destinations studied, tourist motivation variables show a dominant influence, particularly for Jl. Tunjungan, which boasts high historical value and good accessibility. This research can provide a foundation for the Surabaya City Tourism Office and destination managers in designing promotion programs and developing attractions to enhance the city's tourism competitiveness amid regional destination competition